Qualitative and Quantitative Estimation or Chemical Constituents from Leaves and Roots of Iraqi Agave Attenuata by GC-MS and RP-HPLC(Conference Paper) # - Shah, Sherine Majeed; Thukaa Z. Abdul-Jalil (Iraqi Journal of Pharmaceutical Sciences, 2023)
This research concentrate on cultivated Iraqi Agave attenuata dried leaves and roots, because of little studies on this plant especially on the root that lead to the eager of study and comparison of phytochemical constituents between leaves and root. Extraction of bioactive constituents was carried out using several solvents with increasing polarity (n-hexane, ethyl acetate and methanol) by soxhlet apparatus. Steroidal saponins in Agave genus is well documented in many species, lightening the minds in this research on extraction method which is specific for steroidal saponins. Phytochemical screening was done by GC/MS for n-hexane fraction, qualitative and quantitative estimation of several bioactive constituents (caffeic acid, p-coumaric acid, and quercetin) for ethyl acetate and methanol fractions while for steroidal saponins (sarsasapogenin, hecogenin and tigogenin) in both leaves and root by using reverse phase-high performance liquid chromatography (RP-HPLC). Among those identified phytochemical constituents, several constituents have not been detected in Agave attenuata leaves and roots before. This study is the first to describe the results in which the highest concentration of caffeic acid was found in leaves ethyl acetate fraction, p-coumaric acid and quercetin in root ethyl acetate fractions. While for steroidal saponins, the hecogenin, tigogenin and sarsasapogenin highest concentrations were found in leaves.